Training on Writing Good and Correct Indonesian for MSMEs in Merah Putih Village, STM Hulu District, Deli Serdang Regency - Elly Romy; Herlin Munthe (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
The use of good and correct Indonesian plays an important role in increasing the professionalism and consumer trust in Micro, Small, and Medium Enterprises (MSMEs). However, many MSMEs still do not apply proper linguistic rules in writing promotional media, product labels, and written business communications. Therefore, this community service activity aims to improve the understanding and skills of MSMEs in writing Indonesian in accordance with applicable rules. The methods used in this activity include lectures, discussions, and direct practice. This service was carried out at the Merah Putih village cooperative in STM Hulu district, Deli Serdang Regency. This service was carried out on November 17, 2025. The results of the activity showed an increase in participants' understanding of the use of good and correct Indonesian as well as their ability to produce clearer, polite, and professional business writing. Thus, this training is expected to support the improvement of business image and competitiveness of MSMEs through quality written communication.